HUBUNGAN KARAKTERISITIK IBU HAMIL DENGAN ANEMIA DI DESA LAT DALAM TAHUN 2024 - Saragih, Kristiova Masnita; Wahyunita, Vina Dwi (Jurnal Maternitas Kebidanan, 2024)
Anemia in pregnancy is a decrease in hemoglobin concentration below 11.0 g/dl. Anemia in pregnancy is still a major problem of maternal mortality in almost all developing countries in the world. In Indonesia, anemia is a problem in women as a result of iron and folic acid deficiencies. The impact of anemia on pregnant women is various kinds of complications for the mother, in the form of disorders during pregnancy (inadequate gestational weight gain, abortion, prematurity); disorders during labor (uterine atony, prolonged labor, bleeding); as well as disorders during the postpartum period (vulnerability to infection and stress due to decreased body immunity, low breast milk production); the most serious is maternal death. The aim of this study was to determine the relationship between characteristics of pregnant women and anemia in Lat Dalam Village. This research uses data collection methods from questionnaires obtained directly from pregnant women. The characteristics of pregnant women obtained were, age, education, child spacing (parity), pregnancy spacing and nutritional status of pregnant women. Then, the data in this study were processed using the SPSS program and analyzed using univariate and bivariate analysis using the Chi-Square test with α= 0.050. The results of the analysis showed that of the 30 respondents, 7 people (53.8%) had anemia at the age of ≤20 years, 6 people had a high school education (46.1%), 7 people had ≤ 1 child ( 53.8%), pregnancy interval ≤ 1 year was 6 people (46.2%), KEK nutritional status was 5 people (38.5%). There is a significant relationship between education (p value = 0.04; p value <0.05) and nutritional status of pregnant women (p value = 0.02; p value <0.05) with the incidence of anemia in pregnant women. There is no significant relationship between age (p value = 0.15; p value > 0.05), child spacing (parity) (p value = 0.40; p value > 0.05), pregnancy spacing (p value = 0.17; p value >0.05) with the incidence of anemia in pregnant women. It is hoped that the pustu or community health center will carry out antenatal care (ANC) examinations and check hemoglobin levels on pregnant women who visit the pustu or community health center.